Крохальский серпантин - Мамин Николай Иванович (Серия "Аллея", 2021)
Экземпляры: ЦБ (20230529) / Инвентарный номер: 59523 / Цена: 638.00 / Сис.шифр: 84(2=411.2)6 / Авт.знак: М 22 / ГРНТИ: 17.82 / ББК: 84(2=411.2)6-44